Desain Karakter untuk Video “Menjaga Kesehatan Mata” dengan Teknik Motion Graphic - Melati, Na’ima Dinda; Sutejo, Aris; Wulandari, Sri (Innovative: Journal Of Social Science Research, 2024)
Currently, the rapid development of technology causes children to use tablets and cellphones more often. This condition can also become worse because children have a higher risk of developing myopic eyes. It is very necessary to provide education regarding eye health, one of which is for children. Cultivating the habit of maintaining eye health from an early age can have a good impact on children's future. Therefore, there is a need for educational media delivered by health institutions such as community health centers to elementary schools when carrying out health screening. So, children can understand how to maintain eye health. The method used is a qualitative method with primary and secondary data collection techniques. Primary data collection is through interviews, observations, Focus Group Discussions and Observations, while secondary data collection is through literature. The result of this design is characters that are used for eye health educational videos using motion graphics techniques.